The mediating role of innovation in the impact of entrepreneurial bricolage on SME performance in the tourism sector - Kustiningsih, Nanik; Andayani, Wuryan; gati, Vidia; Kuswandi, Kuswandi; Sidarta, Alphasyah Lazuardy (Edelweiss Applied Science and Technology, 2024)
This study examines the mediating role of innovation in the relationship between entrepreneurial bricolage and the performance of small and medium-sized enterprises (SMEs) in the tourism sector. The research examines how resource-limited SMEs utilize creative problem-solving and resource optimization to enhance their competitive advantage. The study adopts a quantitative approach. Data was collected through surveys and in-depth interviews, data were collected from 46 SMEs in East Java, Indonesia, path analysis reveals that innovation significantly enhances the positive impact of bricolage on SME performance. Path analysis was employed to examine the direct and indirect effects of entrepreneurial bricolage on SME performance, with innovation as the mediating variable. The results demonstrate that entrepreneurial bricolage significantly improves SME performance by fostering innovation, which acts as a crucial mediator. SMEs practicing bricolage are able to optimize limited resources creatively, leading to innovative products, processes, and marketing strategies that enhance competitiveness and performance in the tourism sector. The findings provide practical implications for SME owners and policymakers in resource-constrained environments, offering strategies to leverage creativity and innovation for competitive advantage. The study provides valuable insights for SMEs, policymakers, and researchers. SMEs are encouraged to adopt bricolage as a strategic tool to navigate resource constraints, while policymakers should support innovation by improving resource accessibility and providing training programs. Future research can expand on this study by exploring bricolage practices across different regions and sectors, as well as investigating the long-term impact on SME performance. This research contributes to the limited literature on entrepreneurial bricolage in tourism SMEs, particularly in developing regions such as East Java. It offers new insights into how SMEs can leverage internal capabilities and innovation to achieve sustainable growth and maintain a competitive edge in resource-constrained environments.